Analisis Interaksi Obat Antidiabetik terhadap Clinical Outcome Pasien DM Tipe 2 di RS X Jambi - Dewi, Rasmala; Hadriyati, Armini; Situngkir, Euryke Novalisa (Universitas Baiturrahim, 2025)
Diabetes mellitus (DM) type 2 is a chronic disease that requires continuous treatment, resulting in drug interactions. Drug interactions are one of the drug related problems identified as drug therapy events that can affect the patient's clinical outcome. The aim of the research is to determine the number of potential drug interactions in type 2 DM patients and the relationship between drug interactions and clinical outcomes in the form of achieving blood glucose control targets. This research was conducted using a descriptive analytical method with a cross-sectional design. Data were collected on type 2 DM patients in outpatient care at Hospital Data analysis of the relationship between therapy and clinical outcomes used the chi-square test. The results of the study found that 41 patients (89%) experienced drug interactions, 5 patients (11%) did not experience drug interactions. Based on this data, 138 cases could be identified, consisting of 91 cases (66%) of pharmacodynamic interaction mechanisms, 46 cases (34%) of pharmacokinetics, with 18 cases (13%) of minor severity, 114 cases (83%) of moderate severity. and major in 6 cases (4%). The most frequent interactions were candesartan and lantus with 9 cases (7%) and candesartan and novorapid with 9 cases (7%). Patients achieved clinical outcomes for blood glucose in 22 patients (48%) and 24 patients (52%) achieved uncontrollable blood glucose clinical outcomes. The results of the analysis carried out stated that there was a relationship between drug interactions and patient clinical outcomes in the form of controlled blood glucose control targets, p-value <0.013.